Adverse childhood experiences and life opportunities: Shifting the narrative. (January 2017) - Metzler, Marilyn; Merrick, Melissa T.; Klevens, Joanne; Ports, Katie A.; Ford, Derek C.
Abstract: Substantial research shows that early adversity, including child abuse and neglect, is associated with diminished health across the life course and across generations. Less well understood is the relationship between early adversity and adult socioeconomic status, including education, employment, and income. Collectively, these outcomes provide an indication of overall life opportunity. We analyzed data from 10 states and the District of Columbia that used the adverse childhood experiences (ACE) module in the 2010 Behavioral Risk Factor Surveillance System to examine the association between ACEs and adult education, employment, and income. Compared to participants with no ACEs, those with higher ACE scores were more likely to report high school non-completion, unemployment, and living in a household below the federal poverty level. This evidence suggests that preventing early adversity may impact health and life opportunities that reverberate across generations. Current efforts to prevent early adversity might be more successful if they broaden public and professional understanding (i.e., the narrative) of the links between early adversity and poverty. We discuss our findings within the context of structural policies and processes that may further contribute to the intergenerational continuity of child abuse and neglect and poverty. Highlights: Adverse childhood experiences are negatively associated with adult education, employment, and income potential. Understanding the potential impact of early adversity across the life course is critical to breaking the intergenerational cycle of poverty. Assuring the healthy development of all children is essential for societies seeking to achieve their full health, social, and economic potential.